High Performance Electrolyte Using Mixtures of Ionic Liquid – Solvent for Sodium-Ion Batteries. (19th June 2018) - Le, Linh Thi My; Vo, Thanh Duy; Nguyen, Quan D.; Okada, Shigeto; Alloin, Fannie; Le, Phung My Loan
Abstract : The use of ionic liquids-based electrolyte can solve the safety problems associated with lithium/sodium ion batteries, especially for large-scale applications due to its thermal stability and inflammability. The main challenge of ionic liquids is relatively high viscosity and the using of organic solvent at suitable content could be an alternative solution for reducing viscosity, meanwhile, the electrochemical properties as well as the good thermal stability the mixed solutions keep similarly to the pure ionic liquid. In this study, electrolyte mixtures based on EMITFSI with organic solvents (EC and PC) were prepared and evaluated the electrochemical compatibility in half-cell configuration with respect to sodium metal anode and using electrode materials: SnS/C, hard carbon (HC) and Na0.44 MnO2 . Moreover, the thermal stability, the flammability and the conduction mechanism of electrolyte mixtures were also explored and discussed.